Full body harness - Wan Manan, Wan Majidah; Che Senu, Nur Syazana; Othman, Siti Amira (Penerbit UTHM, 2020)
The full body safety harness is a key part of an active fall arrest system. The harness serves two purposes, first, distributing fall forces safely across a worker's body in the event of a free fall, and second, providing freedom of movement sufficient to allow the worker to effectively perform his or her job. The complete body harness incorporates the characteristics of a sit harness that supports the hips and upper legs as well as a chest harness that supports the chest and shoulders. The complete body structure includes the human torso when correctly used and helps to keep it upright during a fall case.